Membangun Jembatan: Komunikasi Misi Kristen untuk Generasi Alfa - Pasaribu, Ferdinan (Sekolah Tinggi Teologi Sriwijaya, 2025)
There are challenges in communication of missions to Generation Alpha. This research aims to explore effective ways to build communication bridges for Christian missions in the context of Generation Alpha. This generation, comprising children born between 2010 and 2025, is growing up in a digital era with unlimited access to information. Therefore, traditional approaches to Christian missions need to be adjusted to be more relevant to them. A qualitative method is used in this study to understand Generation Alpha's views on spirituality and how social media and technology can be utilized to convey mission messages. Through this study, it is hoped that effective strategies can be identified to create more inclusive and engaging communication for Generation Alpha. The research findings indicate that to build communication bridges for Christian missions for this generation, the following are necessary: first, the use of technology and social media; second, interactive approaches; third, relevant education; fourth, community development; and fifth, appreciation of generational differences. In conclusion, building communication bridges for Christian missions for Generation Alpha requires innovative and relevant approaches.